Sociological, demographic and economic study of the Indigenous communities in the Ucayali Region: 1993-2007 - Díaz Encinas, Alida Isidora (2015)
The communities indigenous from region Ucayali have social, demographic and economic characteristics very different from other urban centers in our country even different from other communities and etnias in the same region. To know this reality will allow us to propose guidelines that will direct the social policies for the above mentioned populations. In this article we check the situation from diverse approaches, trying to know in a detailed way the reality lived by the above mentioned populations, his failings, his expectations and the future that waits for them from the decisions that they themselves carry out.